COMPARATIVE ADVANTAGE BETWEEN CONVENTIONAL BANK AND ISLAMIC BANK ON CORPORATE SOCIAL RASPONSIBILITY (CSR) - SANI ABDULLAHI SULE (Khazanah: Jurnal Mahasiswa, 2022)
Both conventional and Islamic banking has been in the market system for almost 50 years, since it began during the 1960s. Since that time, both conventional and Islamic banking has quick grown and is no longer a strange concept. The products and services provided have been well accepted, not only among Muslim countries and also non-Muslim countries. However, there is a lack of comparative between conventional bank and Islamic bank performance in terms of corporate social responsibility (CSR). The paper aims to analyze the relationship between Islamic bank and conventional bank on their CSR performance. It is a conceptual attempt to discuss on how Islamic principles can influence the implementation of CSR in both conventional bank and Islamic banking system. The religious expect both the conventional bank and Islamic bank to have the strong influence to attract customers by using CSR. For that reason, this paper tries to investigate the relevant literature views and the relationship between conventional bank and Islamic bank concept on CSR. The paper try to find that, the concept of Islamic bank that comply with religious provision should exhibit more proactive CSR activity and policies. Islamic bank performance should be superior to conventional bank counterpart.